2016
DOI: 10.1515/raon-2015-0045
|View full text |Cite
|
Sign up to set email alerts
|

Survival of patients with intermediate stage hepatocellular carcinoma treated with superselective transarterial chemoembolization using doxorubicin-loaded DC Bead under cone-beam computed tomography control

Abstract: BackgroundThe purpose of this retrospective study was to evaluate treatment response, adverse events and survival rates of patients with intermediate stage HCC treated with superselective doxorubicin-loaded DC Bead transarterial chemoembolization (DEBDOX) under cone beam computed tomography (CBCT) control.Patients and methodsBetween October 2010 and June 2012, 35 consecutive patients with intermediate stage HCC (32 male, 3 female; average age, 67.5 ± 7.8 years; 22 patients Child-Pugh class A, 8 class B, 5 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 35 publications
(74 reference statements)
1
18
0
Order By: Relevance
“…Due to heterogeneity of the patient population tumor response and survival rates are variable. 1 , 4 , 5 , 9 , 10 , 11 The overall response rate for TACE treatment is about 50%, with the lowest reported around 15% and the highest around 85.6% 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 Reported 1-, 2- and 3-year survival rates range from 37% to 91.5%, 14% to 75% and 58.8% to 71.4%, respectively. 1 , 3 , 4 Current prognostic factors for determination of treatment response and survival in patients treated with TACE are mainly based on clinical assessment and are included in the BCLC classification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to heterogeneity of the patient population tumor response and survival rates are variable. 1 , 4 , 5 , 9 , 10 , 11 The overall response rate for TACE treatment is about 50%, with the lowest reported around 15% and the highest around 85.6% 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 Reported 1-, 2- and 3-year survival rates range from 37% to 91.5%, 14% to 75% and 58.8% to 71.4%, respectively. 1 , 3 , 4 Current prognostic factors for determination of treatment response and survival in patients treated with TACE are mainly based on clinical assessment and are included in the BCLC classification.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 Lately a new embolization agent called drug-eluting bead (DEB) has been introduced and several clinical studies have confirmed the benefits of DEBTACE with respect to improved tumor response, reduced adverse effects and improved survival. 2 , 3 , 4 , 5 , 6 , 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug-eluting microsphere transcatheter arterial chemoembolization is a safe procedure for patients with HCC, with reports showing low rates of serious complications (1.6–7.2%) (2051). These complications included hepatic insufficiency or infarction, liver abscess, tumor rupture, bile duct injury, cholecystitis, upper gastrointestinal bleeding, pleural effusion, pulmonary embolism, splenic infarction, and spinal embolization.…”
Section: Complications Safety and Survivalmentioning
confidence: 99%
“…The CR and ORR of DEB-TACE in HCC patients realize a range of approximately 32% to 42.4% and 51% to 94.5% in several previous studies, displaying good treatment responses. [1517] While for RFA, previous studies indicate responses rates of RFA in HCC patients with a CR range roughly at 20% to 90%. [1820] Prior studies show that combining TACE with RFA realizes relatively encouraging treatment responses.…”
Section: Discussionmentioning
confidence: 99%